The Influence Of Financial Literacy, Investment Risk And Investment Motivation On Investment Interest In The Capital Market (Survey of Students of the Faculty of Economics and Business Universitas Perjuangan Tasikmalaya) - Larasati, Ayu; Yusnita, Rita Tri; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine whether financial literacy, investment risk and investment motivation simultaneously and partially affect student interest in investing in the capital market. This research design is quantitative. The population in this study were students of the Management and Accounting Study Program at Universitas Perjuangan Tasikmalaya. The sample in this study were 100 students. Data collection in this study using the questionnaire method. Then test the data with multiple linear regression analysis with SPSS Version 25. The results showed that Simultaneously Financial Literacy, Investment Risk and Investment Motivation have a significant effect on Investment Interest in Students of the Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya. Partially Financial Literacy, and Investment Motivation have a significant influence on Investment Interest in Students of the Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya. Meanwhile, Investment Risk does not have a significant influence on Investment Interest in Students of the Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya.